FAMILY BUSINESSES IN UKRAINE AND ABROAD: COMPARISON OF RESEARCH AREAS - Alieksieiev, Ihor; Węcławski, Jerzy; Kurylo, Oksana; Chaus, Olha (Socio-economic relations in the digital society, 2023)
The purpose of the article is to compare the research areas of family businesses in Ukraine and abroad. The article examines the domestic and foreign research experience of family businesses from the standpoint of innovative economic development. Relevant publications of recent years are considered, which reflect the results of research and achievements of science and practice of the leading countries of the world, and a typology of family business research is compiled. The author’s features of the typology of research on family enterprises are proposed: resource-oriented research, innovation-management and project research, approbation-methodical research, spatial and credit-oriented research, and innovation-oriented integrating research. As a means of implementing programs, projects, and measures for the development of family enterprises, planning and organizational measures of innovatively oriented formation, functioning and development of family enterprises and determination of optimal ways of such development are proposed. The problems of the creation, operation and development of family enterprises in Ukraine and the development of family entrepreneurship on the basis of modern innovations and experience of foreign family firms of various types of economic activity were considered. This will allow, in the current conditions, as well as in the post-war period, to use the potential of family businesses of all types of economic activity in the most effective way. The article proposes the use of methods of analysis, analogy, comparison, induction, and statistics, which allowed to thoroughly study a certain set of issues and draw appropriate conclusions.